Assistência domiciliar de enfermagem ao bebê nascido com muito baixo peso e sua família - Sassá, Anelize Helena (2011)
The fragile condition of babies born with very low birth weight (BBVLBW) at their home interferes with their recovery and development process. They require more specialized care than that provided to babies born with adequate weight and/or in good health conditions. After discharge from hospital, these children are highly vulnerable due to their preterm birth and very low birth weight. Their families are also vulnerable since they face new factors, or rather, taking care of the preterm child at home requires some kind of life adaptation. Each family is unique and faces the process in its own way. It is important to know and to understand their behavior, their feelings, and the meaning of such experience. Current analysis tries to understand the experience of families experiences in BBVLBW home care during the first six months after hospital discharge. Research included a descriptive qualitative approach that employed the methodological reference Convergent Care Research Approach. Study comprised nine families whose BBVLBW were assisted over the first six months after hospital discharge. Data were collected between June 2010 and August 2011 through informal and semi-structured interviews and by participants observation conducted during home visits to the families. Data were analyzed according to content analysis proposed by Bardin. The Calgary Family Assessment Model was also employed to describe the family structure and social support given to the families. Results showed that taking care of preterm children requires family strength and courage to overcome insecurities arising from baby hospitalization and fragility. The mother os possibility of staying with her BBVLBW during hospitalization, although representing an important period of approximation between mother and her baby and providing experience on how to deal with the child at home, was not enough to ensure confidence in taking care of her preterm baby by herself. In this context, the difficulties faced by the family, which constituted the focus of nursing care, mainly consisted of explanations on doubts with regard to preterm babies peculiarities, breastfeeding management and BBVLBW feeding, coupled to family caretaking and home organization for the newly-born child. The presence of a support network by the entire family, friends, community and health care professional services benefitted the family's equilibrium and mitigated the difficulties experienced during the care process. As the fears and anxieties related to care and conditions of BBVLBW were overcome by the families, they felt safer to transfer the demands of baby care from hospital staff to themselves. Nursing care at home benefitted families adaptation and allowed them to be assisted according to needs at home. It also reassured and strengthened them to overcome difficult times and to experience a new phase within the family life cycle.